Viscoelastic behavior of an epoxy resin during cure below the glass transition temperature: Characterization and modeling. (January 2019) - Courtois, Alice; Hirsekorn, Martin; Benavente, Maria; Jaillon, Agathe; Marcin, Lionel; Ruiz, Edu; Lévesque, Martin
This paper presents a viscoelastic temperature- and degree-of-cure-dependent constitutive model for an epoxy resin. Multi-temperature relaxation tests on fully and partially cured rectangular epoxy specimens were conducted in a dynamic mechanical analysis apparatus with a three-point bending clamp. Master curves were constructed from the relaxation test results based on the time–temperature superposition hypothesis. The influence of the degree of cure was included through the cure-dependent glass transition temperature which was used as reference temperature for the shift factors. The model parameters were optimized by minimization of the differences between the model predictions and the experimental data. The model predictions were successfully validated against an independent creep-like strain history over which the temperature varied.